An analysis of long-term pile load tests in permafrost from the Short Range Radar site foundations - Biggar, Kevin W; Kong, Vivien (Canadian Geotechnical Journal, 2001)
During the installation of the Short Range Radar (SRR) facilities at 35 sites across the Canadian Arctic, in excess of 7 000 piles were installed for the SRR foundations. A total of 137 pile load tests were performed during the SRR construction. Only a small number of these were installed external to the foundations and were loaded well in excess of design loads to attempt to determine their ultimate load carrying capacity. Only eight of these piles were loaded for extended durations (>12 h). This paper presents the results of these long-term load tests and compares the results with design guidelines based on allowable pile deformations and creep in ice-rich, saline permafrost. In nonsaline permafrost, at high normalized displacement rates (>30 year 1 ) the stresses on the piles at failure were less than those predicted by design guidelines for piles in ice-rich soil. At lower normalized displacement rates (<15 year 1 ) the failure stresses on the piles were reasonably well predicted by the design guidelines. Significant reductions in pile capacity were observed in ice-rich, saline permafrost. Without detailed knowledge of the unfrozen water content in the soil, however, prediction of the behaviour of the piles could only be bounded by current design guidelines.Key Words: permafrost, field pile testing, cold-temperature grout, long-term creep.